Using a quantum dot bead-based lateral flow immunoassay to broadly detect the adulteration of PDE-5 inhibitors in functional foods. Issue 26 (20th June 2022) - Song, Mingshu; Wu, Qin; Liu, Beibei; Li, Pan; Jiang, Lan; Wang, Yulong; Dong, Sa; Xiong, Yonghua; Hammock, Bruce D.; Zhang, Cunzheng
Abstract : A quantum dot bead-based lateral flow immunoassay was developed for the simultaneous determination of PDE-5 inhibitors based on a broad recognition monoclonal antibody, which was successfully employed for the inspection of function food. Abstract : In this study, a designed hapten possessing the classic structure of PDE-5 inhibitors was synthesized. A monoclonal antibody (mAb) with broad recognition for six PDE-5 inhibitors was further produced. For the determination of lodenafil, methisosildenafil, mirodenafil, udenafil and tadalafil, the limit of detection (LOD) and IC50 ranged from 1.01 to 26.91 ng mL −1 and 12.75 to 278 ng mL −1, respectively. Thereafter, a quantum dot bead-based lateral flow immunoassay (QB-LFIA) was developed, which improved the LOD and IC50 to 0.32–6.52 ng mL −1 and 7.45–133.8 ng mL −1, respectively. Method validation was conducted using honey and capsule samples spiked with PDE-5 inhibitors, and the recoveries of the intra- and inter-assays ranged from 81.01% to 108.16%, with coefficients of variation below 12.71%. In addition, the validity and the consistency have been confirmed with a comparison between QB-LFIA and HPLC-MS/MS ( R 2 = 0.9957). Furthermore, the developed QB-LFIA was employed for the inspection of real products, and several samples were found to be adulterated with lodenafil and methisosildenafil.